KNOWLEDGE ATTITUDE AND PRACTICE TOWARD COVID-19 DISEASE AMONG VARIOUS PROFESSIONALS: A CROSS-SECTIONAL ONLINE SURVEY - S, ABEETHA; RAMYA K; N, BHAGYASHREE; S, SUMA; V, SUREKA; KOTHARI, ASHUTOSH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: This study aims to assess the knowledge, attitude, and practice associated with COVID-19 disease by undertaking a web-based online survey. Methods: A cross-sectional survey was conducted all over India during the initial phase of COVID-19 hit between March 19, 2020, and March 29, 2020. Anyone aged 18 years and above using social media were included in the study. The questionnaire had a section on sociodemography which had questions regarding age, gender, marital status, and occupation. This was followed by questions on knowledge, attitude, and practice regarding the COVID-19 pandemic. The knowledge scores were summarized as median with interquartile range as the data followed a non-normal distribution. Attitude and practice questions were summarized individually as proportions and its association with socio-demographic variables was established using Chi-square test. The statistical significance was set at p<0.05. Results: Occupational groups, marital status, and age group had significant difference between the groups with at least one of the practices with p<0.05. Conclusion: Since the study provides enhancing effect of knowledge toward protective behaviors, the awareness raising activities and health education through mass media and campaigns, this should urgently be conducted focusing on effectiveness of hand washing, cough etiquette, social distancing, and responsibility to inform suspected cases to local health authority to prevent COVID-19.